PENEGAKAN HUKUM DALAM PENGADAAN BARANG DAN JASA PEMERINTAH OLEH KOMISI PENGAWAS PERSAINGAN USAHA (KPPU) DAN KOMISI PEMBERANTASAN KORUPSI (KPK) - Adam Khafi Ferdinand; Sunarto DM; Maya Shafira (Universitas Lampung, 2020)
Conspiracy of tender and corruption are both have related in government’s procurements of goods and services, because the procure partially or completely are being financed by APBN/APBD or another state budgeter. The act in the conspiracy of tender also is categorized as an act of corruptions. Therefore, there are two law enforcement institutions which have the authority to punish the perpetrators, that are KPPU and KPK. The purpose from this journal is to find out about how the efforts in law enforcement on government’s procurements of goods and services by KPPU and KPK, and what are the influence factors in the law enforcements process. This research is used with law normative method which is supported with data and information from interview or questionnaire. Futhermore, these article is using with statue approach and comparative approach. The results from this research are the law enforcement in government’s procurements goods and services by KPPU on tender conspiracy case have implemented of based in Anti Monopoly Law, KPPU Law Number 1 of 2019 and KPPU Law Number 2 of 2010 (Guidelines of Article 22). Whereas, law enforcement in government’s procurements goods and services by KPK on corruption case have implemented of based in Corruption Law, KPK Law and KUHAP. Both institutions have scope and authority for each other, however both of them have cooperation in terms of supervision and the law enforcement in government’s procurements goods and services which is poured on Memorandum of Understanding (MoU) between KPPU and KPK. Other than that, there are many factors that influence the law enforcement in government’s procurements goods and services by KPPU and KPK, there are law factor, law enforcer factor, tools/facilities factor, public factor and culture factor.